Reflux esophagitis in chagasic megaesophagus - Machado, Wellington Monteiro [UNESP]; Machado, PVT; Souza, RMS (Medimond S R L, 2001)
The esophagitis associated with chagasic megaesophagus is commonly attributed to food and secretion stasis, thereby its name of stasis esophagitis. The present work suggests instead that in some chagasic patients the clinical, endoscopic and histological findings are more compatible with a true reflux esophagitis.